2020
DOI: 10.1186/s12903-020-01125-3
|View full text |Cite
|
Sign up to set email alerts
|

Gingival bleeding and calculus among 12-year-old Chinese adolescents: a multilevel analysis

Abstract: Background: Gingivitis is a common oral health problem, and untreated gingivitis can progress to periodontitis. The objectives of this study were to (1) explore associated factors of gingival bleeding and calculus among 12-yearold adolescents; (2) find predictive models for gingivitis management. Methods: Four thousand five hundred twenty-five subjects aged 12 in Sichuan Province were investigated. The questionnaire and clinical examination were applied in schools, and two-level logistic regression models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 53 publications
3
23
1
Order By: Relevance
“…There is limited evidence that smoking promotes human gingival vasoconstriction. 70 The result of the present study revealed that the subjects who visited the dentist had less plaque and gingival index; which is in line with that of Chen et al 49 , who found that more dental visits are good predictors of better gingival status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is limited evidence that smoking promotes human gingival vasoconstriction. 70 The result of the present study revealed that the subjects who visited the dentist had less plaque and gingival index; which is in line with that of Chen et al 49 , who found that more dental visits are good predictors of better gingival status.…”
Section: Discussionsupporting
confidence: 92%
“…Despite our data reported that gender had an impact on bleeding index only, this result is similar to previous study. 48 However, it is in contrast to the findings of the study of Chen et al 49 , which reported gender as a strong determinant for most of the oral health determinants. Some studies 50,51 have reported that the increased level of sex hormones during pregnancy may cause a significant elevation in gingival inflammation (gingival index and bleeding index) in pregnant women, but with no significant differences in plaque scores.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, 40.40% had calculus (21% both subgingival and supragingival), without statistically significant differences between boys and girls. This percentage is lower compared to other studies conducted in 12-year-old children from other countries such as Puerto Rico (61.59%) (17), China (66.94%) (23), and Ecuador (60.5 to 77.9%) (24). Variations may be attributed to differences in methodology of the studies and may also suggest or reflect differences in oral hygiene practices.…”
Section: Discussioncontrasting
confidence: 60%
“…After completing the oral examination, all adolescents received an oral evaluation form to take home. This form classified the child's oral health status according to the severity of the oral findings and recommended the timing of their next dental visit [20,21].…”
Section: Clinical Assessmentmentioning
confidence: 99%